A REVIEW BACKGROUND OF SPECIAL BUILDING REGULATORY IN MALAYSIA - Nurul Sal Shabila Izanda; Salfarina Samsudin; Aminah Mohsin, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Focusing on Malaysia, the development of multi-unit buildings that incorporate numerous ownerships for various sorts of land uses, such as residential, commercial, industrial or mixed-use properties, has been made possible by the phenomena of vertical building construction. Peninsular Malaysia (excluding Sabah and Sarawak) and the Federal Territories of Kuala Lumpur, Putrajaya and Labuan are primarily governed by the Strata Titles Act 1985 (STA 1985), which also applies to the Federal Territories of Kuala Lumpur, Putrajaya and Labuan. The most contentious issue now being debated in stratified development is the non-issuance and transference of strata title to the parcel owner (or purchaser) of the old-stratified scheme. As a result, the amended Strata Titles (Amendment) Act 2007 (Act A1290) has incorporated the 'special building' as a new element in the strata title application to minimize the aforementioned issue in the application. Furthermore, Strata Titles (Amendment) Act 2017 (Act A1518) also has promulgated for any parcel owners to apply for the strata title of their properties. Although the legislation for encountering the non-issuance and transference of strata title is being upgraded, there has been no discernible increase in the number of strata title applications for special building, as certain States have shown no increase in application numbers since the special building is been introduced. Therefore, this paper aims to review the legal aspects of strata title application for special building as stipulated in the Strata Titles Act 1985 to deliver a broad understanding of the special building concept. The research method used is qualitative research which will rely on the analysis of the relevant statutes, rules, regulations, books, journals, articles, thesis, monographs, research grants reports, seminar papers, electronic materials and data internet.